Quadriceps Strength in Patients With Isolated Cartilage Defects of the Knee: Results of Isokinetic Strength Measurements and Their Correlation With Clinical and Functional Results. Issue 5 (26th May 2017) - Hirschmüller, Anja; Andres, Tasja; Schoch, Wolfgang; Baur, Heiner; Konstantinidis, Lukas; Südkamp, Norbert P.; Niemeyer, Philipp
Background: Recent studies have found a significant deficit of maximum quadriceps strength after autologous chondrocyte implantation (ACI) of the knee. However, it is unclear whether muscular strength deficits in patients with cartilage damage exist prior to operative treatment. Purpose: To isokinetically test maximum quadriceps muscle strength and quantify the impact of possible strength deficits on functional and clinical test results. Study Design: Cross-sectional study; Level of evidence, 3. Methods: To identify clinically relevant muscular strength deficits, 24 patients (5 females, 19 males; mean age, 34.5 years; body mass index, 25.9 kg/m 2 ) with isolated cartilage defects (mean onset, 5.05 years; SD, 7.8 years) in the knee joint underwent isokinetic strength measurements. Maximal quadriceps strength was recorded in 3 different testing modes: pure concentric contraction (flexors and extensors alternating work; con1), concentric-eccentric (only the extensors work concentrically and eccentrically; con2), and eccentric contraction in the alternating mode (ecc). Results were compared for functional performance (single-leg hop test), pain scales (visual analog scale [VAS], numeric rating scale [NRS]), self-reported questionnaires (International Knee Documentation Committee [IKDC], Knee Injury and Osteoarthritis Outcome Scale [KOOS]), and defect size (cm 2 ). Results: Compared with the uninjured leg, significantly lower quadriceps strength was detected in the injured leg in all isokinetic working modes (con1 difference, 27.76 N·m [SD 17.47; P = .003]; con2 difference, 21.45 N·m [SD, 18.45; P =.025]; ecc difference, 29.48 N·m [SD, 21.51; P = .001]), with the largest deficits found for eccentric muscle performance. Moderate negative correlations were observed for the subjective pain scales NRS and VAS. The results of the IKDC and KOOS questionnaires showed low, nonsignificant correlations with findings in the isokinetic measurement. Moreover, defect sizes (mean, 3.13 cm 2 ) were of no importance regarding the prediction of the strength deficit. The quadriceps strength deficit between the injured and the uninjured leg was best predicted by the results of the single-leg hop test. Conclusion: Patients with isolated cartilage defects of the knee joint have significant deficits in quadriceps muscle strength of the injured leg compared with the uninjured leg. The single-leg hop test may be used to predict quadriceps strength deficits. Future research should address whether preoperative strength training in patients with cartilage defects of the knee could be effective and should be taken into consideration in addition to surgical treatment.